A review on Ti-based metal matrix composite coatings - Abavi Torghabeh, Naghmeh; Pouriamanesh, Rasoul (Journal of Composites and Compounds, 2022)
Lightweight high-strength Ti-based metal matrix composites (Ti-based MMCs) have a multitude of application applications, e.g., biomedical engineering, aerospace, and automotive, due to their good sustainability, high specific strength/stiffness, high elevated temperature strength, high wear, and corrosion resistance. Although there are metal matrix composite coatings comprised of polymers, composite, and ceramics materials, the paper primarily focuses on titanium-based composite coatings. This review also discusses the different coating techniques including electrodeposition, thermal spray, plasma spray, vapor deposition, and laser cladding to achieve high hardness and roughness, wear resistance and corrosion resistance. Totally, we attempt to bring out Ti based materials scenario for its current applications.